2014
DOI: 10.1590/s0034-759020140609
|View full text |Cite
|
Sign up to set email alerts
|

Dependence relationship between the critical quality factors and social impact

Abstract: This paper shows the results of the empirical study conducted in 186 tourist accommodation businesses in Spain certified under the "Q for Tourist Quality", own System Quality Management. It was raised with the purpose of analyzing the structure of the relationship between critical quality factors and results-social impact, how they operate and the level of their influence on obtaining these results within the company. Starting from a deep theoretical revision we propose a theoretical model together with the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Literature reviews revealed that different fields where: similarities between both approaches seem evident: process orientation; stakeholder focus; commitment; efficacy of resource management; contribution to competitiveness; organizational reputation; long-term planning; and continuous improvement assessment culture" (Mendes and Dias, 2018, p. 274). Some empirical studies have supported the idea that combined TQM-CSR approaches help organizations in achieving competitive advantages (Benavides-Velasco et al, 2014;Chiarini, 2016;Mehralian et al, 2016;Parast and Adams, 2012;A ´lvarez Garcı ´a et al, 2014;Tarı ´, 2011). Benavides-Velasco et al (2014) explained that both TQM and CSR satisfy two main stakeholders (i.e.…”
Section: Components Of the Total Quality Management And Corporate Soc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reviews revealed that different fields where: similarities between both approaches seem evident: process orientation; stakeholder focus; commitment; efficacy of resource management; contribution to competitiveness; organizational reputation; long-term planning; and continuous improvement assessment culture" (Mendes and Dias, 2018, p. 274). Some empirical studies have supported the idea that combined TQM-CSR approaches help organizations in achieving competitive advantages (Benavides-Velasco et al, 2014;Chiarini, 2016;Mehralian et al, 2016;Parast and Adams, 2012;A ´lvarez Garcı ´a et al, 2014;Tarı ´, 2011). Benavides-Velasco et al (2014) explained that both TQM and CSR satisfy two main stakeholders (i.e.…”
Section: Components Of the Total Quality Management And Corporate Soc...mentioning
confidence: 99%
“…Some empirical studies have supported the idea that combined TQM-CSR approaches help organizations in achieving competitive advantages (Benavides-Velasco et al , 2014; Chiarini, 2016; Mehralian et al , 2016; Parast and Adams, 2012; Álvarez García et al , 2014; Tarí, 2011). Benavides-Velasco et al (2014) explained that both TQM and CSR satisfy two main stakeholders (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%